Increase in body weight is lowered when mice received fecal microbiota transfer from donor mice treated with the AT1 receptor antagonist telmisartan - Marco L. Freschi; Axel Künstner; Gianna Huber; Gianna Huber; Gianna Huber; Ines Stölting; Hauke Busch; Misa Hirose; Walter Raasch; Walter Raasch; Walter Raasch (Frontiers Media S.A., 2024)
IntroductionTreatment of rodents with the AT1 blocker (ARB) telmisartan (TEL) has an anti-adipose effect. Among other mechanisms, we also have attributed the anti-adipose action to diet-independent alterations in gut microbiota. Thus, we aimed here to confirm this mechanism by using the fecal microbiota transfer (FMT) approach.MethodsSeven weeks after initiating a high-fat diet (HFD), C57BL/6N mice received fecal microbiota for 8 weeks from donor mice by oral gavage, continuing HFD feeding. Stool samples came from mice that were treated with TEL (8 mg/kg/d by gavage, 12 weeks), thus remaining lean despite HFD feeding (BL/6>fTEL), while controls received feces samples from vehicle/HFD-treated obese mice (BL/6>fVEH). Microbiota of the stool samples from these acceptor mice was analyzed by 16S rRNA gene amplicon sequencing.ResultsWeight gain was lower in BL6>fTEL than in BL6>fVEH mice after 3 but not 8 weeks. Energy homeostasis, insulin sensitivity, and body composition did not differ between the two groups. β-diversity indicated group differences (F = 2.27, p = 0.005). Although the Firmicutes/Bacteroides ratio did not differ, abundances of distinct phyla, families, and genera varied. Among others, Ruminococcaceae and Desulfovibrionaceae, Desulfovibrionia uncl., and Lachnospiraceae uncl. were lower in BL/6>fTEL than in BL/6>fVEH mice. Moreover, the correlation between body weight and Lachnospiraceae, Desulfovibrionaceae, Desulfovibrionia uncl., or Desulfovibrio was positive in BL/6>fVEH and negative in BL/6>fTEL mice.DiscussionAs FMT from TEL-pretreated mice influences the microbiota in acceptor mice with slight weight-reducing effects, we confirm the relevance of TEL-related microbiota changes for weight reduction, most likely independent of the transferred stool-residual TEL effect on the host metabolism.